2013
DOI: 10.4293/108680813x13794522666446
|View full text |Cite
|
Sign up to set email alerts
|

Pneumoperitoneum 48 Days After Laparoscopic Hysterectomy

Abstract: Postlaparoscopic pneumoperitoneum is usually self-limited to a few days. The presence of free air under the diaphragm of a patient with acute abdominal pain 48 days after total laparoscopic hysterectomy prompted an exploratory laparotomy during which no perforations were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, pneumoperitoneum can persist for several days and has been reported to occur 48 d after a total laparoscopic hysterectomy. In this particular patient, an exploratory laparotomy was performed, and there was no evidence of perforation or organic trauma [5]. A single patient in our cohort was found to have pneumoperitoneum on POD 23 and did not require additional surgical intervention.…”
Section: Discussionmentioning
confidence: 91%
“…However, pneumoperitoneum can persist for several days and has been reported to occur 48 d after a total laparoscopic hysterectomy. In this particular patient, an exploratory laparotomy was performed, and there was no evidence of perforation or organic trauma [5]. A single patient in our cohort was found to have pneumoperitoneum on POD 23 and did not require additional surgical intervention.…”
Section: Discussionmentioning
confidence: 91%
“…Evidence suggests that most episodes of residual pneumoperitoneum following laparoscopic surgery resolve within 3 days, with up to 96 % of cases resolving within a maximum of 7 days [4]. However, there have been some individual case reports of patients presenting with acute abdominal pain secondary to post-operative pneumoperitoneum at up to 48 days following the original procedure [5]. This was most likely to be a diagnosis of exclusion, in which no other surgical or non-surgical cause for the pneumoperitoneum could be elicited.…”
Section: Discussionmentioning
confidence: 95%
“…Image evaluations, therefore, generally show small amount of intra-abdominal gas in two or 3 days after operation but extremely rarely present long-lasting intra-abdominal free air beyond postoperative 7 days. Smith et al [ 11 ] reported a patient with prolonged free air observed in 48th day after laparoscopic hysterectomy. Detailed mechanisms of the free air retention in the abdominal cavity for a long time remain uncertain.…”
Section: Discussionmentioning
confidence: 99%